Improving postpartum hemorrhage care: Policy, practice, and research. (28th June 2022) - Ameh, Charles; Althabe, Fernando
Synopsis: Reducing the risk of death from PPH requires evidence‐based care, innovations, and addressing demand and supply‐side bottlenecks around quality, availability, and use of uterotonics.